Therapists’ experiences of working with Iranian-Immigrant IPV clients in the United States - Nikparvar, Fatemeh (Kansas State University, 2019)
Mental health practitioners have a responsibility to provide effective interventions to all their clients, accounting for each client’s cultural context and cultural values relevant to their well-being. In this study, eight therapist who have worked with Iranian-immigrant IPV clients were interviewed to answer two questions: 1) What have therapists who work in the U.S. learned about challenges working with Iranian IPV clients living in the U.S.? and 2) what suggestions do these therapists have for improving services for Iranian IPV clients living in the U.S.? In response to the first question, six main themes were found: a) clients’ lack of knowledge, b) cultural acceptance that men are not accountable for their behaviors/gender norms in patriarchal culture, c) women’s sense of disempowerment (victim’s role), d) clients do not disclose IPV due to a sense of obligation, e) clients’ fear of consequences of disclosing, and f) Clients’ difficulty trusting therapists and the mental health field. In response to the second question (i.e., what suggestions do these therapists have for improving the services for Iranian IPV clients living in the U.S.?), three main themes emerged: a) clients need for knowledge and psychoeducation, b) the services are not sufficient/ not proportional, c) therapists need to have a broad perspective and understanding of clients. Results add to the understanding of IPV grounded in the Iranian immigrant culture and ultimately contribute to a culturally-based conceptualization of IPV among Iranian immigrants to sensitize therapists regarding culturally appropriate interventions that reflect the concerns of the Iranian immigrant community living in the U.S.
Keywords: Intimate partner violence; Cultural sensitive therapy; Iranian-immigrant clients